A Criminalization of Civil Servant in Case of Neutrality Violations in a Regional Head Election - Emmilia Rusdiana; Rizkiyah Putri Maharani (Universitas Negeri Semarang, 2022)
This study aims to validate and analyze the accuracy of sentencing the the defendant as the head of the service in fulfilling the elements of the legal subject as a Civil Servant, as well as legal proof of the defendant's actions which are considered beneficial or detrimental to one of the candidate pairs. Legal research with normative juridical, as well as statutory, case, and conceptual approaches and analyzed prescriptively. The accuracy of sentencing the the defendant in Decision Number 147/Pid.Sus/2018/PN.Sdr regarding legal subjects is based that the Panel of a judge s interprets ASN holding certain positions in government as ASN. The judge's considerations did not refer to the Civil Servant Law and the the defendant was a High Pratama Official, belonging to an Echelon 2 position, and this was based on the theory of a criminal responsibility that the actions taken by the the defendant were a burden of personal responsibility not the responsibility of the position. It has nothing to do with the main duties and official functions as Head of the Social, Civil and Population Registration Service, and not as a legitimate job order task. Legal proof of the the phrase